Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.

Anonymous
Anonymous asked in Science & MathematicsMathematics · 10 years ago

What is (1+√2) (1-√2)?

(1+√2) (1-√2)

are my steps wrong?

1 times 1 = 1

+

1 times -root2 = -root 2

+

positive root2 times 1 = positive root 2

then

For the last step I got that -√2 times √2 = -2 right?

should be 1-root 2 +root 2, those cancel, and -root 2 at the end.

total should be 1-2 = -1

WHAT????? where is the mistake?

8 Answers

Relevance
  • 10 years ago
    Favorite Answer

    (1+√2)

    (1-√2)

    ______

    1 - sq rt of 2

    +sq rt pf 2

    - sq rt of 2 sq =- 2

    Ans 1 - 2 = -1

  • 10 years ago

    (1+√2) (1-√2) =

    1 - √2 + √2 - (√2)² =

    1 - 2 =

    -1

  • ?
    Lv 7
    10 years ago

    YOUR STEPS ARE RIGHT

    (1+√2) (1-(1+√2)

    =[1]^2--[√2 ]^2

    =1--2

    = --1

  • 10 years ago

    You're rigth!

    (1+√2)*(1-√2) = 1 - √2 + √2 - 2 = 1 - 2 = - 1

  • How do you think about the answers? You can sign in to vote the answer.
  • 10 years ago

    i found your problem! -√2 times √2 does not equal -2

    it equals √2^2 (squared)

    and thats just 2

    then youll be left with 1-2 and then -1 as your answer

  • Anonymous
    10 years ago

    No mistake - - - (a+b)(a-b) = a^2-b^2

    in your problem a^2 = 1 and b^2 = 2

  • 10 years ago

    Simple FOIL problem! The answer IS indeed -1!

    Source(s): No source, Went to school!
  • Anonymous
    10 years ago

    Who says -1 is wrong?

Still have questions? Get your answers by asking now.